A study on performance evaluation of Islamic banks in Malaysia: in the Perception of resource mobilization (Deposits) - Rengasamy, Dhanuskodi (Bank Negara Malaysia, Kuala Lumpur, 2017)
The objectives of the study are to examine the performance of Islamic banks in Malaysia through its resource mobilization viz. Deposit ratios and to identify any differences exists between two periods [2011 to 2013 and 2014 to 2016] of bank operation and its performance. This study included all 16 Islamic banks functioning in Malaysia for analysis purpose. The resource mobilization is measured through Financial Ratio Analysis (FRA) such as Credit deposit ratio (CDR), Investment deposit ratio (IDR) and cash to deposit ratio (CTDR). The study is mainly based on secondary data, the data were collected from the annual reports of all banks. The data analysis included descriptive statistics and student’s T-test to calculate data and find difference between two periods’ operation and performance. The outcome of the study indicates that the mean value of CDR for two different periods has been increased. IDR implies the banks needs to concentrate investment of the deposit money. CTDR is volatile because of changes in statutory deposit of banks with BNM. Student’s T-test pointed out majority of the banks have no significant difference between two periods. In overall all Islamicbanks in Malaysia performance in the perception of Deposits is progress during the study period 2011 to 2016.Keywords: IslamicBank, Performance, Deposit Mobilization, Financial Ratio Analysis